Pengaruh Ekspektansi Kinerja, Ekspektansi Usaha, Faktor Sosial Budaya, dan Kondisi yang Memfasilitasi pada Penerapan SIA di LPD Kota Denpasar - Jayanti, Putu Eka; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 27 No 1 (2019)DO - 10.24843/EJA.2019.v27.i01.p20, 2019)
This study aims to examine the factors that influence the interest and behavior of the use of computer-based SIA by using the modified Unified Theory of Acceptance and Use of Technologymodel. This study uses performance expectation variables, business expectations, socio-cultural factors as independent variables and interest in using SIA computer-based as a dependent variable and uses condition variables that facilitate and interest in the use of computer-based SIA as independent variables and computer-based SIA behavior as dependent variables. This research was conducted in Denpasar City LPD. The sampling method uses a purposive sampling technique. Research data was obtained through survey methods with questionnaire techniques. Analysis of research data using multiple linear regression. The results showed that performance expectations, business expectations and socio-cultural factors had a positive effect on the interest in using computer-based AIS as well as Facilitating Conditions and the interest in using computer-based AIS had a positive effect on the behavior of computer-based SIA usage. Keywords : UTAUT, SIA, interests, behavior